Higante museum & community art center - Soliven, Rodolfo II G.; Chua, Johannes Vincent F. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Soliven, Rodolfo G. II Angono, Rizal is the Art Capital of the Philippines, the home of two national artists, the Higantes festival & the first town in the country to be the ASEAN Culture Capital for 2010. Despite its prestigious title and vibrant culture, the town of Angono faces many challenges that inhibit its potential. There is a collective insight among its community about the lack of opportunities and avenues for growth. The municipal government cites "Images-Reality Gap" and "Carrying Capacity" as the primary and most daunting dilemmas of Angono. This thesis aims to address the "Image-Reality Gap" and "Carrying Capacity" among the most pressing issues of Angono. Through an agenda based programming and hybrid approach of sculpture vis-a-vis architecture, the Higante Museum and Community art center shall be developed. This project shall be the first centralized artists facility in Angono focusing on the comprehensive processes of art - from creation to curation. The main objective of this new process is to be able to develop context-based architectural designs, rooted in well-informed design processes and site specific design approaches.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Museums -- Rizal -- Philippines; Arts facilities -- Rizal -- Philippines